A simple linear cavity dual-wavelength fiber laser using AWG as wavelength selective mechanism - Latif, A. A.; Zulkifli, Mohd Zamani; Awang, N. A.; Harun, S.W.; Ahmad, Harith (Institute of Physics Publishing, 2010)
In this paper, a simple design of linear cavity dualwavelength fiber laser (DWFL) is proposed. Operating in the Cband region stretching from 1538.3 nm to 1548.6 nm, an arrayed waveguide grating (AWG) is used to generate the dualwavelengths output together with a broadband fiber Bragg grating as a back reflector and an optical circulator with a 10% output coupling ratio which acts as a front mirror. The measured average output power of the DWFL is about –5.66 dBm and with a side mode suppression ratio (SMSR) of 53.1 dB. The spacing between the two output wavelengths can be varied from 0.8 nm to 10.3 nm with a stable output and minimum power fluctuations.